2020
DOI: 10.1186/s41021-020-00156-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure elucidation of constituents of Citrus limon, Isodon japonicus, and Lansium domesticum as the cancer prevention agents

Abstract: In the course of our research to investigate the cancer prevention potency of natural products derived from plant materials, we isolated fifty-five compounds, including twenty-one new compounds from the peels of Citrus limon, aerial parts of Isodon japonicus, and leaves of Lansium domesticum. The chemical structures of the isolated compounds were elucidated by chemical/physicochemical evidence, and nuclear magnetic resonance spectroscopy and mass spectrometry results. Moreover, the absolute stereochemistry of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Additionally, the fruit has high economic value because the selling price is quite expensive and it is liked by the public for its fresh sweet, and very delicious taste. Also, it has other benefits, which include being an ingredient in cancer prevention ( Matsumoto and Watanabe, 2020 ; Tilaar et al, 2008 ) with the discovery of new compounds in the peel, namely 3-hydroxy-8,14-secogammacera-7, and 14-dien-21-one that exhibits cytotoxic activity that attenuates the MCF-7 breast cancer cell line ( Zulfikar et al, 2020 ). L. domesticum Corr.…”
mentioning
confidence: 99%
“…Additionally, the fruit has high economic value because the selling price is quite expensive and it is liked by the public for its fresh sweet, and very delicious taste. Also, it has other benefits, which include being an ingredient in cancer prevention ( Matsumoto and Watanabe, 2020 ; Tilaar et al, 2008 ) with the discovery of new compounds in the peel, namely 3-hydroxy-8,14-secogammacera-7, and 14-dien-21-one that exhibits cytotoxic activity that attenuates the MCF-7 breast cancer cell line ( Zulfikar et al, 2020 ). L. domesticum Corr.…”
mentioning
confidence: 99%
“…Four new prenylated phloroglucinol isolated from the specie Hypericum erectum Thunb. have potential to increase the effects of various anticancer drugs [28]. 6 The study carried out using the extract of Hypericum longistylum Oliv.…”
Section: Hypericummentioning
confidence: 99%
“…5 The leaf, in particular, contains onoceranoid-type triterpenoids that have anticancer bioactivities such as inhibition of matrix metalloproteinase-2 and antiproliferative activity against human mouth epidermal carcinoma cell line, 4 cytotoxic activity, and antimutagenic activity against Trp-P-1 and PhIP using Salmonella Typhimurium strain. 6 Using liquid chromatography-tandem mass spectrometry (LC-MS/MS) metabolomics, we have previously shown that the L. domesticum hexane, ethyl acetate, and methanol extracts contain phytochemicals that are cytotoxic against A549 lung cancer cells. 7 There is, thus, a promising potential for the medicinal use of lanzones.…”
Section: Introductionmentioning
confidence: 99%
“…Its fruit extract was shown to exhibit apoptosis in human mouth epidermal carcinoma and human colorectal adenocarcinoma cell lines, 3,4 while its fruit peel extract exhibited cytotoxic activity against the epithelial breast cancer cell line 5 . The leaf, in particular, contains onoceranoid‐type triterpenoids that have anticancer bioactivities such as inhibition of matrix metalloproteinase‐2 and antiproliferative activity against human mouth epidermal carcinoma cell line, 4 cytotoxic activity, and antimutagenic activity against Trp‐P‐1 and PhIP using Salmonella Typhimurium strain 6 . Using liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) metabolomics, we have previously shown that the L. domesticum hexane, ethyl acetate, and methanol extracts contain phytochemicals that are cytotoxic against A549 lung cancer cells 7…”
Section: Introductionmentioning
confidence: 99%